Testicular Cancer Risk Awareness in Young Male - María Fernanda Cueva Moncayo; Lexter Mihalache; Edwin Marcelo Miranda (Revista Finlay)
Foundation: testicular cancer is the most common malignant neoplasm in young men and early detection through testicular self-examination is essential. Objective: to evaluate the level of knowledge in young men about testicular cancer. Methods: a descriptive study was carried out. A questionnaire in printed or electronic format was administered anonymously to a sample of 296 male students from various faculties of the Regional Autonomous University of the Andes who were studying in the period 2021-2022. A Chi-square test was used to compare proportions in different subgroups. The level of significance was set at p < 0.05. Data analysis was performed using Statistica software version 13.3. Results: most students showed a lack of prior interest in testicular cancer and had little knowledge about its age of onset, risk factors, and symptoms. Medical students demonstrated greater knowledge on the topic compared to other disciplines. 91 % of male students did not receive information about the risk and importance of testicular self-examination from their doctors. 72 % of students did not seek independent information about testicular cancer. Only 29 % of the students occasionally performed testicular self-examination. Conclusions: young men have poor knowledge about the symptoms of testicular cancer, they have a low frequency of performing testicular self-examination and their doctors do not provide them with information about its importance. It is crucial to disseminate information about testicular cancer among young men, including the topic in high school and university classes, and promoting the regular practice of testicular self-examination.